Diagnosis and successful surgical management of complicated granulosa cell tumour with cystic endometrial hyperplasia in a Beagle dog - Mehra, Shivansh; K.M., Manjusha; Singh, Bhanu Pratap; S.N., Chaithra; Kumar, Sushil; Sarkar, Varun Kumar; S.D., Vinay Kumar; A.T., Faslu Rahman; Saxena, A.C.; Amarpal (Indian Journal of Veterinary Surgery, 2026)
-